600 essential words for the TOEIC test : test of English for international communication - Lougheed, Lin, Dr.; First news. (Tp.HCM : Nxb. Trẻ, 2011)
General business; Office issues; Personnel; Purchasing; Financing and budgeting; Management issues; Restaurants and events; Travel; Entertainment; Health.
Trắc nghiệm tiếng Anh trong giao tiếp quốc tế.
Keywords: English language; TOEIC; English language -- Vocabulary; TOEIC -- Test